2012
DOI: 10.1117/12.909383
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial electrospray for multimodal imaging and image-guided therapy

Abstract: Recent development in multimodal imaging and image-guided therapy requires multifunctional microparticles that encapsulate several imaging and therapeutic agents in the same carrier for simultaneous detection and treatment of the diseases. However, commonly used microfabrication processes for these microparticles have multiple limitations such as the low encapsulation efficiency and the loss of bioactivity for the encapsulated biological cargos. To overcome these limitations, we have carried out both the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Fig. 7d shows that the particles with dual functions were capable of silencing GFP production in 48 h. Si et al (2012, 2013) also demonstrated the loading of drugs and imaging agents in PLGA microparticles, indicating the potential of co-axial electrospray for encapsulation of different drugs and imaging agents within microparticles for multimodal diagnosis and imaging-guided treatment.…”
Section: Applicationsmentioning
confidence: 85%
“…Fig. 7d shows that the particles with dual functions were capable of silencing GFP production in 48 h. Si et al (2012, 2013) also demonstrated the loading of drugs and imaging agents in PLGA microparticles, indicating the potential of co-axial electrospray for encapsulation of different drugs and imaging agents within microparticles for multimodal diagnosis and imaging-guided treatment.…”
Section: Applicationsmentioning
confidence: 85%
“…Otra gran ventaja de EHDA es que se pueden producir partículas mono dispersas. Como se mencionó previamente, las aplicaciones farmacéuticas requieren partículas con un mismo tamaño, y dado a que la velocidad de remoción del solvente es lenta, eso mantiene la integridad de la cápsula (Si, et al, 2012) (Parhi & Suresh) (Benita, 2006).…”
Section: Electroatomización Coaxialunclassified
“…Si et al . used the uniform velocities U i with i = 1, 2, 3 for the inner liquid, the outer liquid and the ambient gas (in this case U 3 = 0) and the uniform axial electric field E 0 [79]. The corresponding dispersion relations were derived and written in an explicit analytical form, and the eigenvalues were computed by numerical methods.…”
Section: Analytical and Numerical Modelsmentioning
confidence: 99%
“…The involved dimensionless parameters include: dimensionless wave number α = kR 2 , dimensionless frequency β = ωR 2 /U 2 , Weber number We = ρ 2 U 2 2 R 2 /γ 2 , dimensionless electrostatic force E = ε 3 E 0 2 /ρ 2 U 2 2 , density ratios S = ρ 1 /ρ 2 and Q = ρ 3 /ρ 2 , velocity ratio U = U 1 /U 2 , diameter ratio R = R 1 /R 2 , electric permittivity ratios ε 1P = ε 1 /ε 3 and ε 2P = ε 2 /ε 3 , conductivity ratio K = K 1 /K 2 , and interfacial tension coefficient ratio γ = γ 1 /γ 2 [79]. The instability analysis yielded the following three unstable modes: paravaricose mode, parasinuous mode and transitional mode.…”
Section: Analytical and Numerical Modelsmentioning
confidence: 99%